Existence of nontrivial solutions for Schrödinger-Kirchhoff type equations involving the fractional p-Laplacian and local nonlinearity - Liu Gao; Chunfang Chen; Jianhua Chen; Chuanxi Zhu (AIMS Mathematics, 2021)
In this paper, we deal with the existence of nontrivial solutions for the following Kirchhoff-type equation